Expression of DNA Methyltransferase Genes in Four-Cell Bovine Embryos Cultured in the Presence of Oviductal Fluid - Barrera, Daniel Florencio (2012)
The possible epigenomic effect of oviductal fluid on expression of DNA methyltransferase (DNMT) genes was examined in early bovine embryos (4-cell stage). Real-time quantitative PCR was performed to determine the relative expression of DNMT1, DNMT3a and DNMT3b transcripts in embryos cultured in vitro in the presence or absence of oviductal fluid. Expression of DNMT1 significantly increased when cultured with oviductal fluid, whereas DNMT3a and DNMT3b transcripts were unaffected by the addition of oviductal fluid. These results may help reveal the role of oviductal factors in the regulation of DNMT expression.